Quantitative DIA-based proteomics unveils ribosomal biogenesis pathways associated with increased final size in three-year-old Chinese mitten crab (Eriocheir sinensis) - Qing Li; Chuanlong Ge; Lijuan Li (BMC Genomics)
Abstract Background Temperature is a key determinant of ectotherms distribution and growth. During the Eriocheir sinensis breeding process, it was observed that crabs in high latitudes and altitude areas with low temperatures undergo diapause, they would overwinter and continue to grow into three-year-old individuals, whose final body size is significantly larger than the normal two-year-old crabs. The hepatopancreas is responsible for maintaining the nutritional balance and energy required for the crab survival. In this study, we aimed to compare the hepatopancreatic proteomic data between three-year-old and two-year-old crabs and clarify the relationship between genes and the final body size phenotype. Results The analysis revealed that differentially expressed proteins were predominantly enriched in essential cellular processes such as ribosome, ribosome biogenesis, RNA degradation, proteasome, mRNA surveillance pathway, and RNA biogenesis. Increasing ribosome usage for protein biosynthesis was found to enhance the crab tolerance to low temperatures and extend their growth period. Simultaneously, the ubiquitin-proteasome pathway was primarily regulated to enhance the degradation of misfolded proteins induced by low temperatures, thus alleviating damage and ultimately resulting in a larger final size for the three-year-old crabs. Conclusion This study provides insights into how low temperatures contribute to individual body size differences and regulate the life cycle, providing a basis for the future artificial breeding of E. sinensis.